EVALUATION OF THE CORROSION INHIBITION POTENTIAL OF RAPHANUS SATIVUS AND SPINACIA OLERACEEA EXTRACTS PART II: MILD STEEL CORROSION INHIBITION BY RAPHANUS SATIVUS AND SPINACIA OLERACEA EXTRACTS AS GREEN CORROSION INHIBITORS - Nicolae Catalin Tampu; Raluca Ioana Tampu; Oana-Irina Patriciu*; Bogdan Alexandru Chiriță; Lucian Gavrilă (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Our study presents the investigation of the inhibitive performances of Spinacia oleracea (spinach) and Raphanus sativus (radish) hydroalcoholic leaves extracts on mild steel corrosion in acidic environments. The spinach and radish leaves extracts were obtained under green conditions (microwave assisted extraction and ethanol as biodegradable solvent). The extracts were added in the corrosive solutions at a concentration of 0.5 g·L-1. The inhibition of the corrosion of mild steel in H2SO4 solution by the plant extracts has been studied using the weight loss method. Both extracts inhibit steel corrosion in 0.1 M H2SO4, but Raphanus sativus extract proved slightly higher corrosion inhibition efficiency (78 %) than Spinacia oleracea the extract (75 %).